Pengaruh Public Trust Terhadap Platform Digital E‑Government dalam Keamanan Data Masyarakat Kelurahan Kalideres (Studi Kasus Pada Aplikasi Jaki Jakarta) - Tiara Rahmawati; Rahma Lia Amanda; Shifa Rosa Apriyani (Journal of Innovative and Creativity (Joecy), 2026)
The digital transformation of public services has encouraged governments to develop various e-government platforms to improve the effectiveness, efficiency, and quality of public service delivery. One of these innovations is the Jakarta Kini (JAKI) application developed by the Provincial Government of DKI Jakarta as an integrated public service platform. Despite the convenience it offers, the use of digital government services has also raised public concerns regarding personal data security. Citizens' perceptions of data security have become an essential factor in building public trust in digital government services. This study aims to analyze the effect of data security on public trust among JAKI users in Kalideres Village, West Jakarta. The study employed a mixed methods approach using a Sequential Explanatory Design, beginning with quantitative research followed by qualitative inquiry to strengthen the interpretation of the findings. The quantitative phase involved 101 respondents selected through purposive sampling. Data were analyzed using simple linear regression with SPSS. Subsequently, qualitative data were collected through in-depth interviews with selected informants. The results indicate that data security has a positive and significant effect on public trust. The coefficient of determination (R²) of 0.857 indicates that data security explains 85.7% of the variation in public trust, while the remaining 14.3% is influenced by other factors outside the research model. Furthermore, the t-test confirms that data security significantly affects public trust with a significance value of <0.001. These findings suggest that stronger perceptions of data security contribute to higher levels of public trust in digital government platforms.